You have a notification: the role of push notifications in shaping students’ engagement, self-regulation and academic procrastination - Bayram Berkay Mumcu; Ayça Çebi (International Journal of Educational Technology in Higher Education)
Abstract The utilization of learning management systems has become pervasive in online learning processes within higher education, thereby underscoring the significance of students’ capacity to manage their learning processes effectively. Nevertheless, deficiencies in students’ self-regulation skills in online learning environments give rise to significant challenges, including poor time management and procrastination. This study aims to examine the effects of push notifications via mobile devices on students’ self-regulation, engagement, and academic procrastination behaviors. The study was a quasi-experimental intervention with 53 students enrolled at a state university. The intervention involved the regular delivery of push notifications to students via the Moodle mobile application and the analysis of students’ engagement, self-regulation, and procrastination behaviors using log data. The results of the study demonstrated that push notifications enhanced students’ engagement and self-regulation skills while reducing academic procrastination. In light of these findings, it is recommended that push notifications be preferred over email or the messaging system as a notification channel to keep students informed of progress in online learning environments.